Evergreen forest Swamps and their Plant Species Diversity in Kalakad-mundanthurai Tiger Reserve, South Western Ghats, India. - Ganesan, R. (Indian Forester, 2002)
Fresh water swamps dominated by Elaeocarpus venustus Bedd. Are one among the many important habitat types of medium elevation evergreen forests in the southern Western Ghats, India. This is yet another important unique habitat type similar to Myristica swamps in the low elevation evergreen forests of Western Ghats. E. venustus is an endemic plant listed in Red Data book and the habitat is also most threatened due to damming and clearing for plantations in the past. Three types of swamps have been identified based on the distribution of E. venustus and other associated plant species in the swamps. This swampy habitat supports many rare plant species. Trees in the swamps are loaded with various epiphytic plants including orchids compared to the surrounding closed canopy forest. Swamps in the medium devation evergreen forests with E. venustus deserves high priority for conservation as many plants in this unique habitat are rare and endemics.